Phase I/II clinical study on safety and antivascular effects of paclitaxel encapsulated in cationic liposomes for targeted therapy in advanced head and neck cancer. Issue 7 (11th December 2013) - Strieth, Sebastian; Dunau, Christoph; Michaelis, Uwe; Jäger, Lorenz; Gellrich, Donata; Wollenberg, Barbara; Dellian, Marc
Abstract Background The purpose of this phase I/II clinical trial was to test safety and effectiveness of 2 doses of vascular targeting cationic liposomes encapsulating paclitaxel (EndoTAG‐1 [ET]) in human head and neck squamous cell carcinoma (HNSCC). Methods Patients with nonresectable therapy‐refractory HNSCC were recruited for both ET treatment groups (3 or 4 patients per group). In cutaneous metastases, laser Doppler blood flow measurements were conducted during infusions. Results Only adverse events of grade 1 or 2 according to the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI‐CTCAE version 3.0) – in particular fatigue, chills, and hypertension – occurred. Follow‐up tumor volume measurements revealed stable disease in 4 of 5 cases. Reproducible dose‐dependent blood flow reductions in skin metastases during ET infusions provide evidence of biological effectiveness. Conclusion Infusions of ET seem to be safe and further phase II and III studies are warranted to prove efficacy in the treatment of HNSCC. © 2013 Wiley Periodicals, Inc. Head Neck 36: 976–984, 2014